Energy Loss of Proton Beam on Ovary Tumor - Giri, K; Khanal, R. (Journal of Nepal Physical Society, 2019)
Proton beam therapy is more effective method than most common radiation (x-rays or photons) therapy and is a new type of irradiation that destroys the tumor or cancer cells in the human body. In the proton therapy, the beam consists of charged nuclei of hydrogen atoms i.e. hydrogen ions or protons. The beam of proton loses the most of its energy to the targeted tissue like ovary tumor cells, with less impact of healthy tissues and organs. This property of a proton beam makes it ideal for clinical applications. When organ safe keeping is our priority then proton beam therapy is the most effective tool to damage nearby affected tissues. For efficient treatment planning in ovary tumor, the maximal energy loss of proton beam in its tissues must be exactly calculated. The method of computer simulation, SRIM is employed for the calculation of energy loss by energized proton beam irradiation on ovary tumor at a depth of 43.3 mm. The stopping power and range data agrees with standard reference data. 65 Mev energy loss is caused by ionization and the energy loss in various layers viz. skin, adipose tissue, soft muscle and ovary are approximately 2.6 MeV, 15 MeV, 7 MeVand 40 MeV respectively, ensuring less injury to healthy cells.